ANALISIS HAMBATAN PENAMBAHAN STERN FLAP PADA KAPAL PATROLI PENGAWAS PERIKANAN MENGGUNAKAN COMPUTATIONAL FLUID DYNAMIC - Aziz, Abdul; Indria Dwi Puspita, Hery; Sakinah, Wazirotus; ., Sumarji; Sutjahjono, Hary; Setiawan, Digdo Listyadi (STATOR: Jurnal Ilmiah Teknik Mesin, 2025)
This study aims to analyze the addition of Stern flap to the performance of fisheries surveillance patrol vessels using Computional Fluid Dynamics (CFD). Stern flap is an additional component on the hull installed at the stern of the ship and serves to reduce the resistance that occurs on the ship. The design or simulation used to compile this research is a literature study, with the Computational Fluid Dynamics method using ANSYS Workbench for Student 2023 R2 software simulation. This study discusses the analysis, simulation, and research results related to hydrostatic and aerodynamic resistance on patrol boat models with and without the use of stern flaps at speed variations from 10 knots to 25 knots. The results show that the use of stern flaps increases hydrostatic resistance at low speeds, but can reduce aerodynamic resistance at high speeds. The comparison shows a significant increase in hydrostatic resistance at low speed with the highest value at 10 knots of 54%, while a decrease in aerodynamic resistance occurs at high speed, especially at 25 knots with a decrease of 23%. These results provide important insights in patrol boat design for performance optimization at various operational speeds.